In-Bag Dry- vs. Wet-Aged Lamb: Quality, Consumer Acceptability, Oxidative Stability and In Vitro Digestibility - Zhang, R; Yoo, MJY; Realini, CE; Staincliffe, M; Farouk, MM (My University, 2020)
The aim of this study was to produce in-bag dry-aged lamb and compare its meat quality, consumer acceptability, oxidative stability and in vitro digestibility to the wet-aged equivalents. Significantly higher pH, weight loss and reduced cook loss were observed in dry-aged lamb compared to the wet-aged (p < 0.0001). Dry-aged lamb had harder and chewier texture profiles and lower colour attributes (L*, a* and b*) than the wet-aged (p < 0.001). The dry-aged and wet-aged lamb were equally preferred (around 40% each) by the consumer panel, underpinning the niche nature of dry-aged meat. Significantly (p < 0.05) higher yeast and thiobarbituric acid reactive substances (TABRS) levels were observed in dry-aged lamb compared to the wet-aged. There was no difference in fatty acid profile, protein carbonyl content and pattern of proteolysis between ageing regimes (p > 0.05). Ageing regimes had no impact on overall digestibility; however, a greater gastric digestibility was observed in dry-aged lamb through the increased release of free amino acids (FAAs) compared to the wet-aged. Outcomes of this study demonstrated for the first time the possibility of producing dry-aged lamb legs of acceptable quality, oxidative stability and superior digestibility compared to the equivalent wet-aged lamb.
Keywords: Consumer acceptability; Digestibility; Free amino acids; In-bag dry-ageing; Lamb chops; Lipid oxidation; Protein carbonyl